Trait selection matters! A study on European amphibian functional diversity patterns. Issue 1 (18th December 2018) - Tsianou, Mariana A.; Kallimanis, Athanasios S.
Abstract: Trait‐based approaches and functional diversity have been previously used to enlighten our knowledge on the structure of community assemblages which are driven by species interactions or abiotic factors. We assess what amphibian functional diversity implies for the community assembly of amphibians of Europe and whether the use of different Functional Trait Groups (FTGs) affects the results. We used presence/absence atlas with 50 km × 50 km grain size and three functional diversity indices (FRic, RaoQ and FDiv) which reflect functional richness and divergence to estimate functional diversity patterns calculated for three FTGs: Morphological, Habitat‐related, Reproductive and the complete set of traits. To identify the two key processes (environmental filtering and limiting similarity) that may shape amphibian communities and how the relative importance of these processes could change using different FTGs, we used null models to test for non‐random patterns of functional diversity accounting or not for the difference in regional species pool. We show that for the same grid cell, for one FTG we might observe lower than randomly expected functional diversity (i.e., trait convergence or environmental filtering as the dominant community assembly process) while for another FTG or for the complete set of traits, higher than randomly expected functional diversity (i.e., trait divergence or limiting similarity as the dominant community assembly process). This highlights the role of trait selection on the inference drawn regarding community assembly. Furthermore, the number of traits (complete set vs. FTGs) used to quantify functional diversity also affects the conclusions regarding community assembly. Abstract : We assess what amphibian functional diversity implies for the community assembly of amphibians of Europe and whether the use of different Functional Trait Groups (FTGs) affect the results. We show that for the same grid cell, for one FTG we might observe lower than randomly expected functional diversity (i.e. trait convergence or environmental filtering as the dominant community assembly process) while for another FTG or for the complete set of traits, higher than randomly expected functional diversity (i.e. trait divergence or limiting similarity as dominant community assembly process).